Strategy to Increase the Procurement Governance Index Value on E-Purchasing Indicators - Taufik, Achmad; Karunia, Luki; Sutrisno, Edy (Yayasan Sinergi Kawula Muda, 2025)
This study aims to identify the causes of the Procurement Governance Index (ITKP) value, especially in the e-purchasing indicator, which is still 0 and how to develop a strategy to increase the ITKP value for the e-purchasing indicator within the Ministry of Health. The method used is a qualitative method by conducting interviews and also reviewing documents. The results of the study found that there are factors that cause the ITKP value for the e-purchasing indicator to be 0, including procedural factors that have not been carried out to completion, human resource factors that still have difficulty in dividing the time to complete administrative work on the system, method factors that circulars and socialization have been made ineffective, and external factors, namely bar/service providers who also have a hand in completing the e-purchasing package. The recommended strategy for problem solving is to provide socialization and technical guidance on the flow of the e-purchasing implementation process by a special work team, in addition, applications/monitoring tools can be created to help monitor the implementation of the e-purchasing package, recalculate the workload to ensure the quality of administrative completion work on the system, and conduct socialization to PPK/PP to add clauses to the contract related to the provider's obligation to complete administrative obligations on the electronic catalog system.